LEKSIKON DALAM LIVE TIKTOK PADA BARANG THRIFT - Dwiyana, Lala; Mualafina, Rawinda Fitrotul; Mukhlis, Mukhlis (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2025)
The objective of this research is to describe the forms of language variation that emerge in TikTok live broadcasts selling thrifted (second-hand) goods, specifically clothing. This study employs a qualitative descriptive method. The data source comprises several TikTok accounts that specialize in selling thrifted clothes, with the data consisting of utterances from the hosts and comments from consumers. Data was collected using a non-participatory observation method with note-taking techniques. Data analysis was conducted using the contextual method (metode padan), where language phenomena are explained by extralinguistic factors. The results of the analysis are presented informally using plain-word descriptions. The findings show that the language variations can be classified into two main forms: lexicon formation processes and brand name disguise. The lexicon formation processes include vocalic or consonantal modification, reduplication, abbreviation, and affixation. Meanwhile, brand name disguise is achieved through phonological modification and descriptions based on logo association. The emergence of this vocabulary variety serves four main functions: to comply with the platform's code of conduct, to create distinctive forms of expression, as a marketing strategy, and to build buyer commitment.